Analisis Determinan Partisipasi Sekolah di Provinsi Jambi - Amalia Pangesti Arum; Melty Roza Adry (Universitas Negeri Padang, 2020)
This study aims to determine and analyze the determinants of school participation in Jambi Province. This research is descriptive and associative research. This study uses primary data, namely using data from the 2018 SUSENAS results. This study uses logistic regression analysis. The results of this study indicate that: partially (1) age and parental education have a significant effect on school participation for basic education aged 7-15 years, while education costs, gender, household income, number of household members, and area of residence does not have a significant effect on school participation for basic education aged 7-15 years in Jambi Province; (2) the cost of education, age, gender, parent's education, and area of residence have a significant effect on school participation for secondary education aged 16-18 years and tertiary education aged 19-24 years, while household income and number of household members does not have a significant effect on secondary school participation aged 16-18 years and tertiary education aged 19-24 years in Jambi Province, and simultaneously (3) all variables used in this study simultaneously have a positive and significant effect on participation schools at all levels of education in Jambi Province